"Defendamos la identidad": campaña de movilización social para la promoción de la ley de identidad de género - Barrios Mujica, Rafael (2021)
The Trans community in Peru currently faces a series of violations to their basic rights, including access to education, work and health. Many of the problems they face are due to an inadequate representation of their gender identity on the National Document of Identification, which is why in 2016 bill n° 790 was proposed by “el Partido Morado”, which addresses this issue. The digital campaign for social mobilization proposed in this project, “Defendamos la Identidad” aims to keep the conversation around the proposed bill alive to ensure that pressure is applied to the political class, leading to the bill finally being debated in congress. The campaign will take place mainly on its own Instagram account, using formats such as posts, stories, animated videos and filters to inform an audience of young people interested in helping the Trans community, in a clear and didactic way about the proposed bill and its importance.